KRITIK DAN SOLUSI TERHADAP SISTEM GANTI RUGI DALAM PEMBEBASAN LAHAN UNTUK KEGIATAN INVESTASI DI INDONESIA (Forum Ilmu Sosial, 2014)
Agrarian conflicts that occurred during the(associated with the influx of investors which caused a lot of losses) isevidence of injustice. Replace the profit represents a new paradigm that has the potential to create fairness, reduce conflic tandimprove the welfare oftheevenly, so that the direction of the purpose of the law it self. Because theold paradig misembeddedin the compensation/demages (for the issue of and acquisition) is not relevant to the values of justiceand expediency.